Application of reverse electrodialysis to site-specific types of saline solutions: A techno-economic assessment. (15th August 2019) - Giacalone, F.; Papapetrou, M.; Kosmadakis, G.; Tamburini, A.; Micale, G.; Cipollina, A.
Abstract: Salinity gradients are a non-conventional source of renewable energy based on the recovery of the Gibbs free energy related to the mixing of solutions at different concentrations. Reverse Electrodialysis is a promising and innovative technology able to convert this energy directly into electric current. The worldwide availability of salinity gradients is limited to those locations where water bodies at different salinity levels are present. The present work analyses a number of different scenarios worldwide, in locations where salinity gradients are naturally available or generated by anthropogenic activities. A techno-economic model of the Reverse Electrodialysis process is presented. The model is used to evaluate the energy that can be harvested in each real scenario using a reverse electrodialysis plant and relevant results are reported in terms of power densities and energy yields. Finally, an economic analysis based on the estimation of the Levelized Cost Of Electricity (LCOE) for each scenario is presented, and perspective considerations are reported. Results suggest that competitive values of LCOE may be achieved in some scenarios. Graphical abstract: Image 1 Highlights: A techno-economic assessment of RED process is presented. Site-specific analysis is carried out, considering different scenarios worldwide. The effect of different stack sizes and membrane properties on RED performances is assessed. For each scenario, LCOE values are evaluated considering different conditions. Future low-cost improved membranes can lead to a competitive LCOE lower than 0.10 €/kWh.